Attitude and labelling preferences towards gene-edited food: a consumer study amongst millennials and Generation Z. Issue 3 (20th November 2020) - Ferrari, Linda; Baum, Chad M.; Banterle, Alessandro; De Steur, Hans
Abstract : Purpose: This study jointly examines consumer attitudes towards gene-edited (GE) food and their preferences for labelling such products. Thus, it contributes to understanding the role of educational background, objective/subjective knowledge, environmental concern and socio-demographics in the context of GE food. Design/methodology/approach: An online survey was administered to two generations of young individuals (millennials and Generation Z; n  = 234) from two neighbouring European Union (EU) regions (Belgium and The Netherlands), which have a stringent policy on (labelling) genetically modified (GM) food. Ordinary least squares (OLS) and ordered logit models (OLMs) were employed to identify key determinants of attitudes towards GE food and GE labelling preferences, respectively. Findings: Attitudes towards GE food were determined by environmental concern (negative) and objective knowledge (positive). Key factors influencing preferences for GE labelling were a non-hard-scientific background, knowledge about relevant policies and a negative attitude towards GE food. Preference for applying a similar labelling policy to both GM and GE was itself linked to having low, objective EU policy-related GM food knowledge and one's nationality. Originality/value: This is one of the first studies to examine consumer attitudes towards GE food products, while also addressing a lack of research on GE food labelling preferences. By highlighting the preferences of young generations for a revised policy approach, this study sheds new light on the current GE debate, notably, by promoting a deeper understanding of a group which has so far received limited attention in the discourse on the acceptance of novel plant-breeding technologies.